Kemijski i mineralni sastav plodova mirte (Myrtus communis L.) - Duralija, Boris; Lozica, Ela; Mikulec, Nataša; Maslov Bandić, Luna; Voća, Sandra (2021)
Mirta (Myrtus communis L.) je tipična samonikla voćna vrsta mediteranske flore, čije plodove već stoljećima lokalno stanovništvo koristi u prehrani i narodnoj medicini. Plodovi mirte najčešće se koriste u prerađevinama, kao što su marmelade, džemovi, vina i likeri, a danas su takvi proizvodi i plodovi samoniklog voća sve više u upotrebi zbog velike zainteresiranosti potrošača za konzumacijom prirodnih proizvoda. U radu je prikazan osnovni opis ove samonikle voćne vrste kao i pregled dosadašnjih istraživanja kemijskog i mineralnog sastava plodova.
Myrtle (Myrtus communis L.) is a typical wild fruit species of the Mediterranean flora, the fruits of which have been used for centuries by the native population in food and folk medicine. Myrtle fruits are most commonly used in processed products such as jams, wines and liqueurs. Nowadays, such products and fruits of wild fruits are increasingly used due to the great interest of consumers in eating natural products. The paper provides a basic description of this type of wild fruit species as well as an overview of previous research on the chemical and mineral composition of the fruits.
Bibliografija: str. 15-16.
Sažetak ; Summary.
Keywords: Mirta -- Myrtus communis L. -- Kemijski sastav -- Mineralni sastav -- Mikroelementi -- Makroelementi